(untitled) (REMUNOM, 2025)
The revolution in the agricultural sector has been strongly driven by technological advancements and the digitalization of the economy. E-commerce platforms focused on agricultural products have emerged as agents of transformation in this context and have redefined the relationships between producers and consumers. This study examines how these platforms are impacting conventional agricultural markets by connecting producers and consumers directly, analyzing their effects on efficiency, identifying the benefits and problems perceived by producers, and assessing future trends. Food production, job creation, and economic development are all influenced by agribusiness, which plays a fundamental role in global economies. Agricultural e-commerce platforms have the potential to eliminate many of these issues, improving system efficiency. This study aims to answer the following question: "How are e-commerce platforms focused on agricultural products impacting the dynamics of traditional agricultural markets by connecting producers and consumers directly?" Specific objectives of this study include analyzing the impact of e-commerce platforms on the efficiency of agricultural markets, investigating the benefits and challenges perceived by producers using these platforms, and identifying future trends and prospects in the agricultural sector related to e-commerce. Given the importance of agribusiness in global economies and the potential of e-commerce platforms to enhance equity and efficiency in agricultural markets, this research holds significant relevance. Its results can inform public policies, business strategies, and decisions of farmers and consumers, contributing to the improvement of the agricultural sector and, consequently, the quality of life of populations.